GCG Dan CSR Sebagai Strategi Peningkatan Nilai Perusahaan: Bukti Pada Perusahaan Go Public Di Indonesia - Ilmi, Mainatul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
The company's goal is to increase corporate profits, prosper shareholders and increase company value. Increasingly high competition among corporations causes companies to become more intelligent to get the attention of investors. Investors in investing choose in companies that can provide maximum benefits. Investors can judge a company through the company's visible value of the company's stock price. Issues for companies that have low corporate value other than due to the company's performance in obtaining a minimal profit is also due to disclosure of corporate governance and corporate social responsibility that has not been adequate and not in accordance with applicable disclosure standards. Disclosure of good corporate governance and social accountability reports that are in line with standards can be a company strategy to increase company value. This can be proven in go public companies in Indonesia.